Microeconomic and macroeconomic influences of entry and exit of firms - Pekka Ilmakunnas; Jukka Topi (Bank of Finland, 1996)
We examine the entry and exit process in the Finnish manufacturing industry.Microeconomic explanations of entry and exit are derived from industrial organization theory and macroeconomic explanations from the theory of monetary transmission mechanism.Since the variables to be explained, the number of entering and exiting firms, are non-negative integers, we use Poisson and negative binomial models in the estimation.The data is a six year panel of three-digit industries.The results show that scale economies form a significant entry barrier, but the evidence on their role as an exit barrier is weaker.Concentration has a negative impact on entry, but this result is not robust to the choice of estimation method.Industry growth has a positive influence on entry and a negative influence on exit, but also variables describing the general economic climate have an influence on the entry-exit process.The variables describing the monetary transmission mechanism have an expected influence on entry. Credit supply has a positive and real interest rate a negative effect on entry.However, the role of the macroeconomic influences on exit is inconclusive.Past entry has a significant effect on exit, which reflects the displacement of old firms by new ones and the short life expectancy of new firms.Both entry and exit have almost unit elasticity with respect to industry size, measured by the number of firms in the previous period.Entry and exit rates are therefore practically independent of industry size.
URN:NBN:fi:bof-20140807458
Keywords: 330; Entry; exit; monetary transmission mechanism